Urdu poetry in Ecological Context - Dr. Tahira Sidddiqua; Dr. Muhammad Naveed (Zaban-o-Adab, 2023)
Ecological movement has impacted political, social and cultural life as well as literature also. In this article, special study of Urdu poetry in respect of effects of ecology movement has been presented in terms of different factors. Like literature of the languages of rest of the world, Urdu literature also records protest against the devestation caused due to lost nature, industrial andtechnological advancement. If we look at the early forms of Urdu poetry, it is known that the style of feeling which was created by the aesthetics of the Bahmani period in the Deccani poetry continued in the Qutb Shahi period and then continued its journey to the Vali Deccani. Remains. The dominance of the linguistic, cultural and aesthetic style of feeling formed by earthly experience is seen overshadowing the entire Deccani literature.